Political Actors and The Socio-Economic Development of The City of Kananga - Muata, Adolphe Kayembe (RADINKA JOURNAL OF SCIENCE AND SYSTEMATIC LITERATURE REVIEW, 2024)
The social reality of the city of Kananga clearly shows that the population's living conditions are not satisfactory. Almost all sectors of life are being destroyed to such an extent that the city has become landlocked. Contrary to this social reality, the city is full of rich natural resources without counting its significant financial and human resources. This article explores Political Actors and the Socio-Economic Development of the City of Kananga. The method used is a literature review, which includes analyzing and evaluating scientific articles and journals relevant to the research problem. This research explains the Thematic study of the Political Actors and the Socio-Economic Development of the City of Kananga. The results of this study show that the strategies proposed to political actors are not comprehensive given the uncertainty of our financial resources. We cannot expand our areas of intervention, in other words, even to enter the regions to see how political actors behave towards the rural world.